ECTHYMA GANGRENOSUM: CASE REPORT OF 5-MONTH-OLD FEMALE - Anwar , Tayyaba; Safdar, Saba; Qaisarani, Salik; Shafique, Ramna; Kanwal , Maria; Haider, Saleha (Journal of Ayub Medical College Abbottabad, 2024)
Ecthyma gangrenosum is a rare and severe skin disease that is typically accompanied by a systemic infection caused by Pseudomonas aeruginosa bacteria. It manifests as painful, necrotic lesions surrounded by redness and including a noticeable black eschar in the centre. The majority of ecthyma gangrenosum instances occur in immunocompromised individuals, such as those with significant underlying medical conditions or those who are neutropenic. We present a case of 5-month-old vaccinated female child, treated for dengue fever 2 weeks back presented to the ER at our facility in a critical state with complaints of pus draining from the right ear, right thigh discoloration and swelling, and swelling of the left cheek, along with difficulty in feeding. On examination, she was afebrile, capillary refill test of more than 4 seconds and random blood sugar of 192 mg/dL. On physical examination, her GCS was 8/15, her pupils were reactive to light, and she was responsive to pain, she appeared pale, and her skin and peripheries were cold. Following the detailed history and physical examination findings, a provisional diagnosis of septic shock and Ecthyma Gangrenosum was established.